MENTORING YOUNG SCIENTISTS IN DEVELOPMENT OF RESEARCH IDEAS: HIGN INTERPROFESSIONAL SUMMER SCHOLARS PROGRAM. (11th November 2018) - Rowe, M; Wu, B
Abstract: Since 1998 the Hartford Institute for Geriatric Nursing has offered a summer program designed to accelerate the development of research projects and trajectories for young scientists. In the week long program, scholars benefit from expert presentations and daily mentoring sessions with experts in gerontological research. In this symposium, scholars will discuss strategies they have used to successfully move from ideas for research, to development of proposals, conduct of research projects and planning career trajectories. We will explore the keys to successful professional mentoring from both the mentor and mentee perspectives. Each scholar will also present their scholarly work with topics including mental health and retirement; traditional Chinese medicine and depression; shared decision-making when living with Alzheimer's disease; frailty associated with surgery in late life; and, improving physical activity in ethnic minority older adults.